A less aggressive approach to the management of super refractory status epilepticus - Madhumathi Gunasekaran; Gowthami Reddi; Ayyammal Palaniappan; Velmurugan Singaravadivelu; Ramakrishnan Tirupur Chinnappan Ramalingam (Wolters Kluwer Medknow Publications, 2021)
Febrile infection-related epilepsy syndrome (FIRES) is a rare catastrophic encephalopathy of unknown etiology. It commonly affects previously healthy children. FIRES is a subcategory of new-onset refractory status epilepticus (NORSE), term used specifically for adult population, and FIRES is used for pediatric population. Uniformly, both FIRES and NORES have poor outcomes with chronic drug-resistant epilepsy, severe neurological sequelae, and mortality in one-fifth of patients. We report a case of FIRES in a 9-year-old previously healthy child in whom a less aggressive approach was used to manage anesthetic resistant super refractory status epilepticus, which has reduced the potentially fatal complications of prolonged use of intravenous anesthetics and also the need for tracheostomy.